Character-based Learning Planning in the 21st Century - Meisuri, Meisuri; Poncowati, Srikandi Dwi; Syarofa, Najwa; Suyitno, Suyitno; Bangun, Eka Uliyanti Putri br (Al-Hijr: Journal of Adulearn World, 2024)
Character-based learning planning is material or tools that teachers must prepare when they want to carry out the teaching and learning process, here the teacher emphasizes more on the affective aspects and character values that are planned to be realized. The purpose of this study is to explain the importance of character-based learning planning in the 21st century, because currently there are still many lessons that do not prioritize character. Researchers used quantitative methods by using google form as a survey tool addressed to teachers in several schools in Tanah Datar. The result of this research is to know that character-based learning in the era of increasingly sophisticated technology is still too little applied, because learning is still adrift to general knowledge that does not prioritize character. The conclusion of this research is that character-based learning in the 21st century really needs to be applied in order to produce students who have good morals. The limitation of this research is that character-based learning materials are only contained in a few subjects, researchers hope that future researchers can develop it further.